Differential effect of Activin A and WNT3a on definitive endoderm differentiation on electrospun nanofibrous PCL scaffold. (12th February 2015) - Hoveizi, Elham; Massumi, Mohammad; Ebrahimi‐barough, Somayeh; Tavakol, Shima; Ai, Jafar
Abstract The first step in the formation of hepatocytes and beta cells is the generation of definitive endoderm (DE) which involves a central issue in developmental biology. Human induced pluripotent stem cells (hiPSCs) have the pluripotency to differentiate into all three germ layers in vitro and have been considered potent candidates for regenerative medicine as an unlimited source of cells for therapeutic applications. In this study, we investigated the differentiating potential of hiPSCs on poly (ε‐caprolactone) (PCL) nanofibrous scaffold into DE cells. Here, we demonstrate directed differentiation of hiPSCs by factors such as Activin A and Wnt3a. The differentiation was determined by immunofluoresence staining with Sox17, FoxA2 and Goosecoid (Gsc) and also by qRT‐PCR analysis. The results of this study showed that hiPSCs, as a new cell source, have the ability to differentiate into DE cells with a high capacity and also demonstrate that three dimension (3D) culture provides a suitable nanoenviroment for growth, proliferation and differentiation of hiPSCs. PCL nanofibrous scaffold with essential supplements, stimulating factors and EB‐derived cells is able to provide a novel method for enhancing functional differentiation of hiPSCs into DE cells.